Analisa Data Pengaruh Akun Instagram @Kulinerkotabatam Terhadap Minat Beli Konsumen - Fendi Hidayat (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2020)
The Instagram account @kulinerkotabatam is an Instagram account that functions to help promote culinary businesses in Batam City. So far, Instagram has been used to promote products / services and photos of its users and not many have promoted culinary delights. In this study, the influence of the @kulinerkotabatam account will be tested on consumer purchase interest using quantitative methods, using random data samples. While the primary data in this study are the results of the answers to the questionnaire and the secondary data used are the results of primary data analysis processed using R Studio software. From the results of data analysis, it is known that the Instagram account @kulinerkotabatam has an influence on consumer buying interest. The results of this study conclude that the independent variable (x) simultaneously has an influence on variable y of 42.88%, the rest is influenced by other factors.